2012
DOI: 10.1038/npp.2012.141
|View full text |Cite
|
Sign up to set email alerts
|

Seizure Susceptibility and Epileptogenesis in a Rat Model of Epilepsy and Depression Co-Morbidity

Abstract: Although a strong co-morbidity exists clinically between epilepsy and depression, the cause of this co-morbidity remains unknown, and a valid animal model is crucial for the identification of underlying mechanisms and the development of a screening tool for novel therapies. Although some rodent models of epilepsy have been reported to display behaviors relevant to affective disorders, the seizure susceptibility of animals prone to depression-like behavior has not been characterized. Toward this end, we assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Animal models support a potential role of pathogenic mechanisms of mood disorders in the development of epileptic seizures and epileptogenesis (Kanner et al, 2014). Depression and manic episodes are described in bipolar disorder and in epilepsy (Kudo et al, 2001;Epps et al, 2012) underlining a bidirectional relationship. Manic attacks in dogs seem to resemble epileptic seizures (Phillips, 2005).…”
Section: Epilepsy Is Linked To Bipolar Disorder and Is Associated Witmentioning
confidence: 94%
“…Animal models support a potential role of pathogenic mechanisms of mood disorders in the development of epileptic seizures and epileptogenesis (Kanner et al, 2014). Depression and manic episodes are described in bipolar disorder and in epilepsy (Kudo et al, 2001;Epps et al, 2012) underlining a bidirectional relationship. Manic attacks in dogs seem to resemble epileptic seizures (Phillips, 2005).…”
Section: Epilepsy Is Linked To Bipolar Disorder and Is Associated Witmentioning
confidence: 94%
“…However, rapid kindling of the ventral hippocampus increased immobility in the FST and decreased saccharin preference, suggestive of a depressive-like phenotype [34]. While we did not see any differences in the rate of amygdala or hippocampal kindling in the SwLo model of depression, these rats did show a profound increase in wet dog shake seizure behaviors during kindling [27]. Combined, these findings suggest that the timing of stimulations, as well as the behavioral endpoint, are important modulators of depression-related behaviors and kindling.…”
Section: Existing Animal Models Of Depression and Epilepsy Comorbimentioning
confidence: 97%
“…A number of studies reported more immobility in the FST several weeks after pilocarpine-induced SE in rats [2026]; researchers also saw a decrease in saccharin preference (when assessed), a further indication of a depression-and anhedonic-like phenotype in these epileptic rats. SwLo rats also demonstrated increased susceptibility to both acute pilocarpine-induced seizures and the appearance of spontaneous seizures 5 weeks following pilocarpine-induced SE [27]. …”
Section: Existing Animal Models Of Depression and Epilepsy Comorbimentioning
confidence: 99%
See 2 more Smart Citations